Prevalence of asymptomatic airflow obstruction among patients visiting a tertiary health-care center - Priya Charan; Reshu Gupta; Prahlad Dhakar (Asian Journal of Medical Sciences, 2022)
Background: Chronic obstructive lung disease is a major health problem worldwide, with a huge impact on health and economics, both at the individual and community levels. In clinical practice, only symptomatic patients seem to undergo spirometry screening, whereas persons with no symptoms or those with early or negligible symptoms are ignored until they present with acute exacerbations and complications. Fair evidence indicates that most individuals with airflow obstruction do not recognize or report symptoms. Aims and Objectives: The present study was conducted to identify the prevalence of undiagnosed airflow obstruction in asymptomatic adults, without known obstructive lung disease or any other pulmonary condition. Materials and Methods: A total of 500 subjects between 18 and 65 years of age, coming to the outpatient department for a routine/preventive health checkup who were asymptomatic and never diagnosed for airflow obstruction, with no evidence of any physical disease on examination were selected by random sampling method after taking informed written consent. A detailed history, complete general physical and clinical examination, and spirometry (as per the ATS guidelines) for individuals were done. Results: Overall prevalence of AO was 16% of patients (80 patients out of 500). About 4.20% of patients had mild obstruction (GOLD – Stage 1), 4.60% had moderate obstruction (GOLD – Stage 2), 5.40% had severe obstruction (GOLD – Stage 3), and 1.80% had very severe obstruction (GOLD – Stage 4). Subjects with asymptomatic airflow obstruction had a higher prevalence of ever smoking (72.5%, 58 out of 80 patients) than never smokers (27.5%, 22 out of 80 patients) and this difference was highly significant statistically. Conclusion: There is a high prevalence of asymptomatic airflow obstruction, detected by spirometry, in asymptomatic patients of different severities. Smoking is a strong risk factor and AO is directly associated with age, both among smokers and never smokers. The use of spirometry should be implemented in all routine health checkup plans, as an important diagnostic tool.